Efektifitas Penggunaan Metode Pembelajaran Simulasi Dengan Latihan Terhadap Keterampilan Pengisian Partograf Pada Mahasiswa Semester II Di Prodi Kebidanan (D-III) Universitas Kadiri Tahun 2015 - Dessy Lutfiasari; Mahmudah Mahmudah (coba, 2015)
The use of the current method of learning very big influence on the growth and development of students' creativity and interest for all subjects to be taught, especially in the use of partograf. From interviews to the 10 students of IV semester Prodi Midwifery (D-III) Kadiri University is known that 4 (40%) of students said it was understood, 4 (40%) of other students say they are confused and 2 (20%) of them said that he was a student not familiar with partograf. This shows the lack of understanding of students in filling partograph. The research objective is to determine the effectiveness of the use of learning methods for skills training simulation with filling partograph the second semester students in Midwifery (D-III) Kadiri University Faculty of Health Sciences in 2015. The research design used is pre experiment with design Static Group Comparison/Posttest Only Control Group Design. The population studied were all students of the second semester in Midwifery (D-III) Faculty of Health Sciences University of Kadiri numbered 50 students and sampling techniques Federer totaled 32 students. This is a research instrument partograph sheet. Results of the study were analyzed using the Mann Whitney test with a significance level of 0.05 were used.The results showed 7 respondents (46.7%) are adept at using partograf with simulation teaching methods and 6 respondents (40.0%) are adept at using partograph with practice learning methods. Data were analyzed by Mann Whitney test obtained ρ = 0.965> α = 0.05 means that H0 is accepted and H1 rejected. This means there is no difference in the effective use of learning methods for skills training simulation with partograph filling. Based on the results of this study are expected to choose the method of learning as a learning method in charging partograph because both methods equally effective. Keywords: simulation methods, drilling methods, partograph filling